1987
DOI: 10.1111/j.1365-2044.1987.tb04106.x
|View full text |Cite
|
Sign up to set email alerts
|

Bradycardia during intra‐abdominal surgery

Abstract: SummaryThe aim of the present study was to examine, in a double-blind, randomised

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A 2007 report of 92 gynecological surgical patients receiving fentanyl, halothane, and vecuronium for major abdominal surgery reported that 18% experienced bradycardia. 1 A 2002 report from Thailand reported bradycardia in 10 of 60 patients (16.6%) having surgical repair of congenital cardiac defects. 2…”
Section: Discussionmentioning
confidence: 99%
“…A 2007 report of 92 gynecological surgical patients receiving fentanyl, halothane, and vecuronium for major abdominal surgery reported that 18% experienced bradycardia. 1 A 2002 report from Thailand reported bradycardia in 10 of 60 patients (16.6%) having surgical repair of congenital cardiac defects. 2…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 , 12 , 14 ] Moreover, anticholinergic administration prior to surgery might prevent vagal overstimulation during surgery that causes severe bradycardia. [ 11 13 ] However, its routine use as a premedication for general anesthesia has been questioned for several reasons. First, irritation of the airway by the anesthetic gas is no longer a concern due to modern anesthetic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Anticholinergic agents such as glycopyrrolate and atropine are indicated in the treatment of perioperative bradyarrhythmia. 11,12 There is evidence that administration of anticholinergic agents in open abdominal or gynaecological surgery, given intravenously prior to induction of general anaesthesia, is effective in the prevention of bradycardia 13 However, their role in the prevention of bradycardia as a result of insufflation of the peritoneum in gynaecological surgery is less defined.…”
Section: Introductionmentioning
confidence: 99%